2017
DOI: 10.1007/s00429-017-1575-z
|View full text |Cite
|
Sign up to set email alerts
|

Repeated shock stress facilitates basolateral amygdala synaptic plasticity through decreased cAMP-specific phosphodiesterase type IV (PDE4) expression

Abstract: Previous studies have shown that exposure to stressful events can enhance fear memory and anxiety-like behavior as well as increase synaptic plasticity in the rat basolateral amygdala (BLA). We have evidence that repeated unpredictable shock stress (USS) elicits a long-lasting increase in anxiety-like behavior in rats, but the cellular mechanisms mediating this response remain unclear. Evidence from recent morphological studies suggests that alterations in the dendritic arbor or spine density of BLA principal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…Acutely, phosphorylation of PDE4s at a conserved C-terminal site by the extracellular signaling regulated kinase (ERK) has been shown to inhibit the activity of so-called PDE4 long forms. [90][91][92] In addition, distinct PDE4 isoforms are down-regulated in a number of pathologic conditions, such as in heart failure or atrial fibrillation, [93][94][95][96] in neurologic conditions such as depression, 97 in cancer 98 during ageing, 93 or in response to stress 99 or drug treatment. 100 In this context, while in the present study, gastroparesis was produced by decreasing PDE4 activity via pharmacologic means, our findings also open the possibility that a physiologic or pathophysiologic downregulation of PDE4 expression and/or activity may be the cause of gastroparesis in a subset of patients, given that the majority of cases remain idiopathic to date.…”
Section: Potential Correlation Of Pde4 Levels and Gastroparesismentioning
confidence: 99%
“…Acutely, phosphorylation of PDE4s at a conserved C-terminal site by the extracellular signaling regulated kinase (ERK) has been shown to inhibit the activity of so-called PDE4 long forms. [90][91][92] In addition, distinct PDE4 isoforms are down-regulated in a number of pathologic conditions, such as in heart failure or atrial fibrillation, [93][94][95][96] in neurologic conditions such as depression, 97 in cancer 98 during ageing, 93 or in response to stress 99 or drug treatment. 100 In this context, while in the present study, gastroparesis was produced by decreasing PDE4 activity via pharmacologic means, our findings also open the possibility that a physiologic or pathophysiologic downregulation of PDE4 expression and/or activity may be the cause of gastroparesis in a subset of patients, given that the majority of cases remain idiopathic to date.…”
Section: Potential Correlation Of Pde4 Levels and Gastroparesismentioning
confidence: 99%
“…Their brains were removed and processed for slice electrophysiology as described previously [25]. Brains were immersed in ice-cold "cutting solution" consisting of (in mM): NaCl (130), NaHCO 3 (30), KCl (3.50), KH 2 PO 4 (1.10), MgCl 2 (6.0), CaCl 2 (1.0), glucose (10), ascorbate (0.4), thiourea (0.8), sodium pyruvate (2.0), and kynurenic acid (2.0).…”
Section: Slice Electrophysiologymentioning
confidence: 99%
“…Individual slices were transferred to a recording chamber and were visualized using a Leica DM6000 FS microscope (Leica Microsystems Inc., Bannockburn, IL, USA) as described previously [25]. Slices were continuously perfused by gravity-fed oxygenated 32 °C aCSF at a flow rate of 2-3 ml/ min.…”
Section: Slice Electrophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanisms underlying plasticity of glutamatergic synaptic transmission in the BLA have been studied under conditions triggering anxiety-like behavioral responses and/or the acquisition and consolidation of fear memories (Manzanares et al, 2005;Ryan et al, 2018). Furthermore, it has been reported that activation of BLA triggered by behavioral training induces a transient increase in mRNA expression of IEGs c-fos, Homer 1a and arc (Knapska et al, 2007;Imamura et al, 2011;Nonaka et al, 2014;Rajbhandari et al, 2016).…”
Section: Discussionmentioning
confidence: 99%